Noise exposure and oxidative balance in auditory and extra-auditory structures in adult and developing animals. Pharmacological approaches aimed to minimize its effects. (July 2016) - Molina, S.J.; Miceli, M.; Guelman, L.R.
Graphical abstract: Abstract: Noise coming from urban traffic, household appliances or discotheques might be as hazardous to the health of exposed people as occupational noise, because may likewise cause hearing loss, changes in hormonal, cardiovascular and immune systems and behavioral alterations. Besides, noise can affect sleep, work performance and productivity as well as communication skills. Moreover, exposure to noise can trigger an oxidative imbalance between reactive oxygen species (ROS) and the activity of antioxidant enzymes in different structures, which can contribute to tissue damage. In this review we systematized the information from reports concerning noise effects on cell oxidative balance in different tissues, focusing on auditory and non-auditory structures. We paid specific attention to in vivo studies, including results obtained in adult and developing subjects. Finally, we discussed the pharmacological strategies tested by different authors aimed to minimize the damaging effects of noise on living beings.